EDMODO IMPACTS: MEDIATING DIGITAL CLASS AND ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Sumardi Sumardi; Muamaroh Muamaroh (LPMPP Universitas Negeri Yogyakarta, 2020)
Information technology-based instruction (e.g. using Edmodo) gains its popularity as it is likely to strengthen the role of teachers, schools, and parents for the sake of optimizing student learning outcomes. Therefore, this study explores how Edmodo was utilized to mediate digital class in English language teaching (ELT); how Edmodo facilitated students' engagement during the class; and how Edmodo mediated teachers to assess students' learning outcomes. A qualitative approach was employed and 286 students from a secondary school voluntarily participated during the study. Interviews, online mini-polling, and document analysis were deployed as data collection methods, and data were validated by triangulation and analyzed by following the interactive model of data analysis. It revealed that Edmodo was an effective mode to mediate digital class in ELT as the students could interact with their teacher, peers, and course contents effectively, both inside and outside the classroom. The students' engagement was also better in comparison to that of the face-to-face classroom. Finally, Edmodo well-mediated teachers to carry out the computer-based test (CBT); it was an accurate mode of assessment as no cheatings were facilitated; the validity, and reliability of the test could be favorably accomplished.